MAPPING TATA KELOLA DOMAIN COBIT 5 PADA PENERAPAN LMS E-LEARNING ITB STIKOM BALI - Dewi, Ni Made Rai Masita; Pramana, Dian; Yusadara, I Gede Putra Mas (Universitas Nusa Cendana, 2024)
The implementation of e-Learning at ITB STIKOM Bali represents a significant support for online learning. The Learning Management System (LMS) called e-Learning ITB STIKOM Bali, based on Moodle LMS, is used to conduct lectures online. e-Learning is integrated with SINAK (Academic Information System), SID (Lecturer Information System), and SION (Online Information System) for both students and lecturers, including course registration and enrollment of students and lecturers. This system is used for both fully online lectures (Asynchronous Learning) and blended learning lectures in all study programs. However, proper maintenance and management of this system are necessary. Therefore, evaluation and analysis in IT governance related to the used LMS are required. In order to measure the maturity level of the e-Learning LMS implementation, measurement based on mapping and measuring the level of capability or gaps is needed. This measurement is conducted using the Process Assessment Model (PAM) within the COBIT 5 framework. Measurement activities will be based on several domains within COBIT 5, with process mapping based on business goals and institutional objectives. Based on the process mapping using PAM, domains strongly related to institutional IT goals focusing on customers and internal aspects are identified: MEA01 (Monitor and Evaluate Performance and Conformance), DSS 03 (Manage Security Services), APO13 (Manage Security), EDM 03 (Ensure Risk Optimization), BAI 07 (Manage Change Acceptance and Transitioning).